Zero to Sixty Plus in 108 Days: Launching a Central Elearning Unit and Its First Faculty Development Program - Monica Orozco; James K Fowlkes; Page Jerzak; Ann Musgrove (Online Learning, 2012)
The Center for eLearning was established at Florida Atlantic University (FAU) as a result of a university-wide task force. A brief overview of the center’s start-up activity is followed by a thorough report of the first faculty development program created and implemented. The structure of the program is described, and data are provided showing evidence of faculty improvement and positive ratings for the program. Conclusions about the program and modifications for its second iteration are included.